Smart Office: Implementing IoT for Enhanced Efficiency and Connectivity - Prastiwi, Yuliana; Hudiono, Hudiono; Imammuddin, Azam Muzakhim (Politeknik Negeri Malang, 2024)
In office buildings, control of electrical devices is still carried out manually using a switch, namely by turning off and turning on electrical devices directly or manually, the result is inefficient and ineffective. To overcome this problem, it is necessary to develop so that electrical control can be carried out automatically and more broadly at the same time can be monitored via a cellphone by utilizing Internet of Things technology. In this study, the implementation of the Internet of Things made in this smart building includes a gate control system using an ultrasonic distance sensor, monitoring light intensity using an LDR light sensor and the condition of the lights in front of the building's terrace, monitoring movement in the room using a PIR motion sensor for control. The use of this technology also covers the field of building security by using fingerprint sensors for office employees. Tests in this study used LDR light sensors which produced a small average error of 0.062%, ultrasonic sensors which produced a percentage of success values of 50% on ultrasonic sensors outside the building, and 70% on ultrasonic sensors in the building area. In testing the PIR motion sensor can detect up to 51 cm which is more than enough to detect movement within the building area. As well as a fingerprint sensor that can be read with a delay of 6 seconds to read fingerprints, update fingerprint sensor data to the database and relay.